Allosteric Modulation of Neurotransmitter Transporters as a Therapeutic Strategy. (July 2020) - Niello, Marco; Gradisch, Ralph; Loland, Claus Juul; Stockner, Thomas; Sitte, Harald H.
Abstract : Neurotransmitter transporters (NTTs) are involved in the fine-tuning of brain neurotransmitter homeostasis. As such, they are implicated in a plethora of complex behaviors, including reward, movement, and cognition. During recent decades, compounds that modulate NTT functions have been developed. Some of them are in clinical use for the management of different neuropsychiatric conditions. The majority of these compounds have been found to selectively interact with the orthosteric site of NTTs. Recently, diverse allosteric sites have been described in a number of NTTs, modulating their function. A more complex NTT pharmacology may be useful in the development of novel therapeutics. Here, we summarize current knowledge on such modulatory allosteric sites, with specific focus on their pharmacological and therapeutic potential. Highlights: Current research is showing an increasing heterogeneity in the binding sites available in NTTs. These binding sites are often located distant from the central binding sites, suggesting a higher level of complexity in the regulation of NTT function. Allosteric sites increase specificity, reducing off-target effects. Small molecules can be developed to target NTT allosteric sites, with the possibility to either increase or decrease their functions. NTT allosteric modulators are in advanced clinical trials, emphasizing their potential for the treatment of neuropsychiatric disorders.